Boundary learning in a gender responsive curriculum transformation in Zimbabwe: an activity theory approach - Charles Chikunda; Plaxcedes Chikunda; Rafael Fonseca de Castro (Universidade do Oeste de Santa Catarina, 2017)
This paper aims to share insights of a boundary learning process in a curriculum transformation in Zimbabwe. It is based on the dialectical lenses of Cultural-Historical Activity Theory (CHAT). The boundary learning epistemic actions were designed/interpreted using CHAT tools of double stimulation, activity system and expansive learning. The main findings are two types of boundary learning: individual and institutional. Individual focused on questioning and confronting tensions in current individual curriculum practice. Institutional refers to collaborative relationships between hierarchical levels of the teacher education system in Zimbabwe. We point to the need for theoretical and conceptual rigor in studies on curriculum transformation, arguing for careful attention to empirical evidence of transformation/transgressing current practices in any expansive learning process. There is also need to think through the policy-practice gap, especially in curriculum development.